PEMBERDAYAAN HUKUM WARIS DALAM PERSPEKTIF MASLAHAH MURSALAH - Hasrul, Muhammad (MADDIKA : Journal of Islamic Family Law, 2023)
This research aims to determine the concept of obligatory will and its application in reviewing maslahah murrasa. Islamic law covers all aspects of human life, for matters in this world and the afterlife. Some contain sanctions and some do not. Legal sanctions are sometimes felt directly in the world like sanctions in general. However, some sanctions are not felt in this world but will be individually responsible for in the afterlife in the form of sin and its retribution. Among the laws governing human relations with others that have been established by God are the rules regarding inheritance. Law regarding the transfer of assets due to death. The existence of inheritance law is very important to regulate the distribution of inheritance regarding who has the right to receive it, how much each share will be, and how it will be distributed. The problems in this research are: (1) How is the obligatory will enforced in Islam? (2) What is the case regarding obligatory wills in religious courts? (3) How is the distribution of substitute heirs in Islam?